Virtual development and production framework for textile orthotics. Issue 7 (3rd July 2017) - Kaiser, Christian; Vogt, Simeon; Tilebein, Meike
Abstract : Customisation is increasingly becoming a necessity in all areas of life. One special field of interest is the area of medical products, as, for example, textile orthotics to enable customer-specific, individualised optimum curing. Current personalisation processes within the development and production processes of textile orthotics barely address the full range of customer diversity. The efficient development and production of customer-specific textile orthotics is not established. Many process steps are currently characterised by manual labour increasing public or private expense. The need for the efficient development and production of customer-specific, diversity-aware orthotics can be realised through virtualised processes. This paper describes the basic characteristics of a virtual development and production framework for the individualisation of textile orthotics with respect to the diversity of customers' characteristics. The computer-aided design (CAD) approaches to adapt dimensions of individualised orthotics and virtually asses fit will be discussed in detail. Digital functionalisation is a flexible module for the production of individualised orthotics and will be introduced in this paper. The reduction of time consumption, the improvement of process flexibility and process performance for the CAD approaches, and the digital funtionalisation will be qualitatively specified.